The Determinants of Capital Structure and Firm Performance - Fudianti, Sely; Wijayanto, Andhi (Universitas Negeri Semarang, 2019)
This study aims to examine the influence of financial and nonfinancial factors affecting the firm performance with capital structure as intervening in manufaturing companies that are listed on the Stock Exchange in 2013-2017. The sample used in this study is manufacturing companies that consist in Indonesian Stock Exchange through 2013-2017.. The method of data collection uses the documentation method from secondary data in the form of annual reports that have been published on the IDX. The data analysis method used is using multiple regression method and sobel test. Financial and non financial factors like sales growth, firm size, board gender diversity, and capital structure influencing firm performance are 92%. This research found that sales growth gives positif effect on firm performance. While, firm size and board of gender diversity have negative effect on firm performance.